The regulation of T helper cell polarization by the diterpenoid fraction of Rhododendron molle based on the JAK/STAT signaling pathway - Qin, JiaXu; Zheng, XiangWei; He, YanChen; Hong, Yang; Liang, Shuang; Fang, Xin (Frontiers in Pharmacology, 2022)
The diterpenoid fraction (DF) prepared from fruit of Rhododendron molle was shown to have potential therapeutic effects on collagen-induced arthritis (CIA) rats based on our previous studies. As a continuation of those studies, herein, a lipopolysaccharide-induced endotoxin shock mouse model was used. The results showed that 0.2 mg/ml of DF significantly increased the mouse survival rate and had an anti-inflammatory effect. Further studies showed that DF could decrease the proportion of T helper cells (Th1 and Th17), and increase the proportion of Th2 and regulatory T cells (Tregs). Enzyme-linked immunosorbent assays indicated that DF inhibited the secretion of inflammatory cytokines such as TNF-α, IL-1β, and IL-6; western blotting showed that DF significantly reduced the levels of phosphorylated STAT1 and STAT3. In vitro, DF could dose-dependently inhibit the polarization of naive CD4+ T cells to Th1 or Th17 cells. DF at 10 μg/ml could markedly decrease the expression of mRNA encoding IFN-γ and T-bet, and suppress Th1 differentiation by downregulation of the activity of STAT1 and STAT4. Meanwhile, DF at 10 μg/ml remarkably reduced the expression of mRNA encoding IL-17a, IL-17f, and RORγt, and downregulated STAT3 phosphorylation, suggesting that DF could inhibit Th17 differentiation by reducing STAT3 activation. Taken together, DF blocked the JAK/STAT signaling pathway by inhibiting STAT1 and STAT3 phosphorylation, which clarified the important role of JAK/STAT signaling pathway in anti-rheumatoid arthritis.